The Effect of Tiktok Social Media Influencer, Brand Image, and Lifestyle on Purchase Intention of Local Skincare Products - Sari, Komala; Sumarwan, Ujang; Munandar, Jono M. (Indonesian Journal of Business and Entrepreneurship, 2024)
This study aims to answer three main objectives. The first is to find out the effectiveness of Tiktok social media influencer endorsements in advertising local skincare products on Tiktok, the influence of Tiktok social media influencers, brand image, and lifestyle on the purchase intention of local skincare products, and managerial implications that can be applied to the local skincare industry. This research was conducted in September and October 2022. The data used in this study came from a questionnaire survey with a Likert scale submitted via a Google form and conducted in Indonesian. Purposive sampling is the selection technique (respondents) used. SEM-PLS is used to process and evaluate data. The survey consisted of 250 respondents, and the findings indicated that each element had a large impact on respondents' intention to purchase local skincare. This research shares an overview and insight that skincare manufacturers can leverage influencer endorsement by using influencers who match the product category they advertise, namely skincare, have good knowledge, an attractive personality, and a positive image. Keywords: brand image, influencer, lifestyle, purchase intention, tiktok social media